INFLUENCE OF TRAINING ON EMPLOYEE PERFORMANCE IS MODERATE BY COMPENSATION IN MILLENIAL GENERATION EMPLOYEES IN BEKASI DISTRICT - Hardianti, Yuni; Gunawan, Ahmad (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
This research was conducted to determine the effect of training on performance which is moderated by compensation for millennial generation employees in Bekasi Regency. This research uses a quantitative method using SPSS Version 26 and MacroProcess version 4.3 with the Hayes 1 model for the analysis method. The population in this research is millennial generation employees who work and live in Bekasi Regency with a total sample of 96 samples. The analysis results show that training has a significant effect on employee performance and compensation as a moderating variable so that compensation significantly moderates the effect of training on employee performance.